2017
DOI: 10.1121/1.4989373
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of a random fibrous medium: Geometry, transport, and sound absorbing properties

Abstract: The main purpose of this article is to present, within a unified framework, a technique based on numerical homogenization, to model the acoustical properties of real fibrous media from their geometrical characteristics and to compare numerical results with experimental data. The authors introduce a reconstruction procedure for a random fibrous medium and use it as a basis for the computation of its geometrical, transport, and sound absorbing properties. The previously ad hoc “fiber anisotropies” and “volume we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Good reviews of some of these models can be found in refs. [4][5][6]. These models can be grouped into two main categories: theoretical models and empirical models.…”
Section: Review Of Previous Work On Airflow Resistivity Modelsmentioning
confidence: 99%
“…Good reviews of some of these models can be found in refs. [4][5][6]. These models can be grouped into two main categories: theoretical models and empirical models.…”
Section: Review Of Previous Work On Airflow Resistivity Modelsmentioning
confidence: 99%
“…Alternatively, in the quest for theoretical understanding, one may seek to better understand the mathematical or physical basis of the generalized Darcy-scale equations for macroscopic transports [9][10][11][12][13][14]. Lastly, one can consider studies based on numerical simulations [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is typically hampered, however, by either the need to simplify geometry [16,18] or physics [15,22]. In recent years, however, another approach to the numerical study of diffusion and fluid flow through fibrous media has gained some popularity [17,23,24]. The idea is to numerically solve the asymptotic behaviors of the linearized Navier-Stokes and heat equations in a realistic microscopically disordered geometry, and then study how volume-averaged properties of the diffusion process and the fluid flow depend on the details of the microstructures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations